Characterization of urea-formaldehyde resins by GPC/SEC and HPLC techniques: Effect of ageing - João M. Ferra (2010)
During the last 40 years, several analytical techniques have been developed/adapted to characterize urea-formaldehyde (UF) resins. However, a great part of the research about this kind of wood adhesives has been performed by industrial producers and, thus, the main part of the existing knowledge is retained within those companies. This work describes a methodology for determining the molecular weight distribution (MWD) of UF resins using Gel Permeation Chromatography (GPC)/Size Exclusion Chromatography (SEC) with 2 detectors (differential refractive index (RI) and differential viscosity). This method permitted to characterize/distinguish commercial UF resins produced with different F/U molar ratios and to monitor the molecular weight and MWD with ageing. An HPLC method was additionally used to evaluate the fraction of unreacted urea, monomethylolurea and dimethylolurea present in commercial UF resins and measure the evolution of these three compounds with ageing. (C) Koninklijke Brill NV, Leiden, 2010